Depósitos a plazo fijo y su incidencia en la rentabilidad de la cooperativa de ahorro y crèdito innovaciòn andina ltda. ubicada en el cantòn Latacunga, provincia de Cotopaxi, en el perìodo econòmico 2013 – 2017. - Vega Ayala, Leticia Maritza (2018)
The popular and solidary economy sector plays an important role at micro financial area. Under the current context and the country's economic crisis, cooperatives in Cotopaxi province Latacunga canton must increase their efficiency, strengthen their solvency and compete on the financial market. The objective of the researching is to determine the incidence oven deposits time on financial and economic profitability of the cooperative, being a fundamental pillar to the sustainability and liquidity of the same. To measure these indices and to determine the degree or percentage of affectation, reasons or indicators of profitability were used. The methodology consisted in the realization of a quantitative study based on the statistical treatment of its financial statements, using a deductive method that allowed to know a truth. In the other hand, the type of researching used was descriptive through graphic analysis and interpretation, as well as correlational research allowed to identify the independent variable such as fixed-term deposits and the dependent variable profitability; by means of these analyzes it was possible to determine the profitability obtained in the Cooperative. The precision of results, the positive relationship between profitability and deposits time or the existence of a negative size defect.